Effects of Three Different Programs of Static and Dynamic Balance Training on Agility, Stability, and Balance in Healthy Male University Students: A Quasi-Experimental Study - Siriworakunsak, Kanruethai; Sengsoon, Praphatson (ASEAN Journal of Rehabilitation Medicine, 2021)
Objectives: To determine the effects of three different programs of static and dynamic balance training on agility, stability, and balance in healthy male university students. Study design: A quasi-experimental design. Setting: Walailak University, Nakhon Si Thammarat, Thailand. Subjects: Thirty-six healthy male university students aged 18-25 years with functional ankle disability index score equal to 100 and body mass index between 18.5-22.9 kg/m2. Methods: The participants were allocated by block randomization into three groups. Group A (n = 9) received static balance training for 6 sessions followed by dynamic balance training for 6 sessions. Group B (n = 11) received dynamic balance training for 6 sessions followed by static balance training for 6 sessions. Group C (n = 12) alternated between static and dynamic balance training for 12 sessions. The participants underwent one position for one session every other day. The total time of the training program was 15 minutes for each session. Agility, ankle stability, and balance before training and after completion of the 12th session were analyzed between the three groups by using one-way ANOVA and within the groups by paired simple t-test and with a p-value < 0.05. Results: There was no significant difference in agility, ankle stability, and balance between the three groups (p > 0.05). When analyzing before training and after completion of the 12th session, a significant difference was found in agility, ankle stability, and balance within Group A, B, and C (p < 0.05). Conclusions: The results of the three training programs were not different. Nevertheless, the three different programs of static and dynamic balance training showed an improvement in all variables after completion of the 12th training session. Therefore, a healthy person can use any of the three different training programs for improving agility, ankle stability, and balance. Keywords: agility, balance, exercise program, lower extremities, stability